PENGARUH BEBAN KERJA DAN TIPE KEPRIBADIAN AUDITOR TERHADAP PENDETEKSIAN KECURANGAN - Ratna Sari (Jurnal Bisnis dan Kewirausahaan, 2022)
This study aims to examine the effect of auditors' workload and personality type on fraud detection at the West Sulawesi Provincial Inspectorate. The population in this study is auditors working in the West Sulawesi Provincial Inspectorate with a total of 85 auditors. Sampling using purposive sampling techniques and obtained a sample number of 60 respondents. The data in this study used primary data collected by distributing questionnaires to all respondents. The data that has been collected will be analyzed through several stages of testing, including descriptive statistical tests, research instrument tests consisting of (validity tests, reliability tests), classical assumption tests consisting of (normality tests, multicollinearity tests, heteroscedasticity tests) and testing all hypotheses proposed in this study and will be proven through coefficient of determination tests, partial tests and simultaneous tests. The results showed that the Workload variable had a positive and significant effect on Fraud Detection in the West Sulawesi Provincial Inspectorate. This result means that the greater the workload the auditor has, the greater the ability to detect fraud that the auditor has in the West Sulawesi Provincial Inspectorate. And the Personality Type variable has a positive and significant effect on Fraud Detection in the West Sulawesi Provincial Inspectorate. This result means that the higher the personality type of the auditor will affect the higher the ability to detect fraud in the West Sulawesi Provincial Inspectorate.